A wideband reflectarray antenna using single‐layer dipole element attached with T‐shaped stubs. Issue 8 (1st April 2019) - Guo, Lu; Yu, Huiting; Che, Wenquan; Yang, Wanchen
Abstract: A wideband reflectarray antenna consisting of single‐layer dipole element attached with T‐shaped stubs is proposed. By varying the lengths of the T‐shaped stubs, the unit cell can provide a linear phase curve covering about 420°. Critical design parameters are analyzed to understand its wideband operating mechanism. Using this novel type of unit cells, a 441 element 25° offset‐fed reflectarray with grid spacing of λ /3 at 10 GHz is designed, fabricated, and measured. The experimental results show that the proposed reflectarray can achieve 1‐dB gain bandwidth of 24% and 1.5‐dB gain bandwidth of 37%. In addition, aperture efficiency of 66.6% and cross polarization level of 29 dB are obtained at 10 GHz, respectively.